"Race Is a Fiction; Racism Is Not"? Understandings of Race in Antiracist Education. Issue 2 (12th August 2021) - Bynum, Gregory
Abstract: Philosophers and other scholars writing on the idea of race have pointed to a tension, in society and in intellectual life, between (1) an understanding of race as an experienced identity, the experience of which must not be denied in the interest of both social justice and critical attentiveness to social structures of racist oppression; and (2) the idea that "race" is a fiction — that, in light of ever‐increasing biological and genetic evidence, race is a clearly inadequate and inappropriate way of categorizing human beings, an oppressive, unjust, and inhumane myth. In this conflicted situation, how should educators, and educational philosophers in particular, respond to racism? Gregory Bynum takes this as the central question of his article: Should educators move away from a view of race as defining people's identities to an understanding of race as a fiction, to be relegated to the past?